Illuminative evaluation of mathematics curriculum implementation in improving students’ numeracy achievement - Jose Bonatua Hasibuan; Deni Darmawan; Suhendra Suhendra; Deni Kurniawan (Institute of Advanced Engineering and Science, 2026)
Persistent evidence from national and international assessments indicates that students’ numeracy achievement remains low, suggesting a gap between intended curriculum goals and classroom implementation. This study conducts an illuminative evaluation of secondary mathematics curriculum implementation as an instructional system, examining how curriculum enactment relates to students’ numeracy achievement in the Indonesian secondary context. Employing a sequential explanatory mixed-methods design, the quantitative phase assessed the numeracy performance of 288 secondary students across content domains, cognitive levels, and item formats, while the qualitative phase investigated instructional practices, assessment culture, and the school learning milieu to explain the observed achievement patterns. The findings indicate uneven numeracy achievement, with performance concentrated at procedural levels and declining from knowing to applying and reasoning. Students perform relatively better on objective formats but demonstrate a limited ability to justify solutions in open-ended tasks. Qualitative evidence further indicates a misalignment between reasoning-oriented curriculum intentions and efficiency-driven classroom practices that emphasize procedural accuracy. These findings provide evidence-based insights into aligning curriculum design, classroom instruction, and assessment practices to strengthen reasoning-oriented numeracy learning.